Determinants of Shareholders’ Profitability in Nepalese Commercial Banks - Lamichhane, Pitamber (Butwal Campus Journal, 2022)
This paper aims to examine impact of bank-specific factors on shareholders’ profitability in Nepalese banks for the period 2009/10 to 2018/19. In this paper, various univariate and multivariate regression models have been used to examine the impact of various explanatory variables on shareholders’ profitability. Return on equity has been used as dependent variable to measure the profitability and bank loans, deposits, capital ratio, credit risk and assets size have been used as explanatory variables. Results of this paper indicate bank loan, deposits and equity capital have positive relationship with shareholders’ profitability. Moreover, findings of the study report inverse effect of credit risk and assets size on shareholders’ profitability. Based on the results, this study concludes that equity capital and credit risk of banks have significant impact on shareholders’ profitability of commercial banks in Nepal. Policy makers can apply findings of this study to formulate and implement effective bank policies to use more equity capital and control credit risk of banks for maximization of shareholders’ profitability.